Amidation of 1, 3-diarylallylic compounds catalysed by 2, 3-dichloro-5, 6-dicyano-1, 4-benzoquinone with molecular oxygen as the terminal oxidant. (1st March 2016) - Cheng, Dongping; Zhou, Xiayi; Yuan, Kun; Yan, Jizhong
An efficient amidation has been developed of 1, 3-diarylpropenes by carboxamides, sulfonamides, carbamates and anilines catalysed by 2, 3-dichloro-5, 6-dicyano-1, 4-benzoquinone and benzoyl peroxide with molecular oxygen. The corresponding products were obtained in moderate to good yields.